Національні та міжнародні стандарти обліку для державного сектору: особливості застосування - Смірнова, І. В.; Смірнова, Н. В.; Смирнова, И. В.; Смирнова, Н. В.; Smirnova, I.; Smirnova, N. (ЦНТУ, 2018)
У статті узагальнені передумови реформування системи бухгалтерського обліку в державному секторі у світі та в Україні. Уточнено зміст категорії «державний сектор». Досліджено етапи міжнародної та вітчизняної стандартизації бухгалтерського обліку в державному секторі, зокрема, щодо запровадження міжнародних та національних стандартів бухгалтерського обліку для державного сектору. Запропоновані напрямки удосконалення нормативно-правової бази з бухгалтерського обліку та фінансової звітності в державному секторі. В статье обобщенные предпосылки реформирования системы бухгалтерского учета в государственном секторе в мире и в Украине. Уточнено содержание категории «государственный сектор». Исследованы этапы международной и отечественной стандартизации бухгалтерского учета в государственном секторе, в частности, разработка международных и национальных стандартов бухгалтерского учета для государственного сектора. Предложенные направления совершенствования нормативно-правовой базы бухгалтерского учета и финансовой отчетности в государственном секторе. In the sphere of of public finance, the reform of the management system confirms the close linkage of measures aimed at achieving the effective use of budget funds, with the improvement of management methods, methodological and methodological provision of accounting and financial control. Accordingly, for Ukraine, it is useful to borrow a systematic approach in developing the legal and regulatory framework for the budget process, accounting and control. In order to create reliable and objective economic information, the process of introducing common standards of accounting and financial reporting continues in Ukraine and in the world. Therefore, the aim of writing of the article consists in finding out of features of application of requirements of international and national public sector accounting standards. Pre-conditions of reformation of the system of accounting in public sector in the world and in Ukraine were generalized in the article. Table of contents of category «a public sector» was specified. The features of development and input of international public sector accounting standards were investigational. The stages of national standardization of accounting in a public sector were systematized. A comparative analysis of international and national public sector accounting standards was conducted. Directions of improvement of normative base from а accounting and financial reporting in a public sector were offered. Positive results in development of methodology of accounting in a public sector can be attain only as a result of only approaches to accounting. One of the basic stages of reform here are application in practice of already existent national public sector accounting standards and development of new. National public sector accounting standards are based on the conceptual provisions of international standards, which contain common methodological approaches to the assessment and disclosure of information. They are in line with international standards, taking into account socio-economic development of the country and the peculiarities of the national budget legislation. The development of methodological recommendations for the introduction of national public sector accounting standards, as well as the review of regulatory and methodological support for the implementation of budget execution operations, taking into account changes in the accounting system, should be undertaken to continue the implementation of reforms in the public sector and bring it closer to international practice.
Национальные и международные стандарты учета для государственного сектора: особенности применения
National and International Public Sector Accounting Standards: Features of Application
Keywords: бухгалтерський облік; фінансова звітність; державний сектор; стандарти бухгалтерського обліку і фінансової звітності; глобалізація; стандартизація; бухгалтерский учет; финансовая отчетность; государственный сектор; стандарты бухгалтерского учета и финансовой отчетности; глобализация; стандартизация; accounting; financial reporting; public sector; standards of accounting and financial reporting; globalization; standardization